High-throughput phenotypic assessment of cardiac physiology in four commonly used inbred mouse strains - Moreth, Kristin; Fischer, Ralf; Fuchs, Helmut; Gailus-Durner, Valérie; Wurst, Wolfgang; Katus, Hugo; Bekeredjian, Raffi; Hrabě de Angelis, Martin (Journal of comparative physiology. B, Biochemical, systemic, and environmental physiology, 2014)
Mice with genetic alterations are used in heart research as model systems of human diseases. In the last decade there was a marked increase in the recognition of genetic diversity within inbred mouse strains. Increasing numbers of inbred mouse strains and substrains and analytical variation of cardiac phenotyping methods require reproducible, high-throughput methods to standardize murine cardiovascular physiology. We describe methods for non-invasive, reliable, easy and fast to perform echocardiography and electrocardiography on awake mice. This method can be used for primary screening of the murine cardiovascular system in large-scale analysis. We provide insights into the physiological divergence of C57BL/6N, C57BL/6J, C3HeB/FeJ and 129P2/OlaHsd mouse hearts and define the expected normal values. Our report highlights that compared to the other three strains tested C57BL/6N hearts reveal features of heart failure such as hypertrophy and reduced contractile function. We found several features of the mouse ECG to be under genetic control and obtained several strain-specific differences in cardiac structure and function.
Gesehen am 07.09.2020